1996
DOI: 10.1366/0003702963905006
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization and Tissue Imaging Using Site-Selective Polyazacyclic Terbium(III) Chelates

Abstract: Polyazamacrocyclic chelates of terbium are shown to be useful in diagnostic medical imaging as tissue site-selective markers. Spectroscopic properties and biodistribution are studied for three terbium(III) species: 3,6,9-tris(methylene phosphonic acid n-butyl ester)-3,6,9,15-tetraaza-bicyclo[9.3.1]pentadeca-1(15),11,13-triene (abbreviated as PCTMB); 3,6,9-tris(methylene phosphonic acid)-3,6,9,15-tetraazabicyclo[9.3.1]pentadeca-1(13),11,13-triene (abbreviated as PCTMP); and N,N'-bis(methylene phosphonic acid)-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…The luminescent Tb(III) complexes possess high quantum yields 72 and supporting studies reported the use of 153 Sm complexes which showed localisation in bone tissue of rats. 73 It is noteworthy that related coordination chemistry with 90 Y has been reported with PCTMB (Fig. 8).…”
Section: Macrocyclic Ligand Derivativessupporting
confidence: 56%
“…The luminescent Tb(III) complexes possess high quantum yields 72 and supporting studies reported the use of 153 Sm complexes which showed localisation in bone tissue of rats. 73 It is noteworthy that related coordination chemistry with 90 Y has been reported with PCTMB (Fig. 8).…”
Section: Macrocyclic Ligand Derivativessupporting
confidence: 56%
“…[25] Tb III -based chelates have also proved useful, as exemplified by a lipid-conjugated chelate that functions as a membrane-staining agent in morphological studies of Swiss albino mouse 3T3 cultured cells, [22] or by Bornhops high brightness macrocyclic labels for in vitro and in vivo analysis of abnormal tissues. [18,26,27] More recently, Parker and co-workers have designed Eu III complexes that specifically stain the nucleoli of several cell lines (CHO, COS, NIH 3T3, HeLa, and HDF). [15,[28][29][30] Most lanthanide ions are also paramagnetic and possess an anisotropic susceptibility tensor that makes them useful for the structural investigation of axial complexes [31] or proteins [32] by NMR spectroscopy, while Gd III has emerged as a universal contrast agent for 3D imaging of biological structures (MRI).…”
Section: IIImentioning
confidence: 99%
“…The suitability of a lipid‐conjugated Tb III chelate as a membrane‐staining agent for morphological studies of Swiss albino mouse 3T3 cultured cells was also demonstrated 20 . In parallel, Bornhop and colleagues have developed high‐brightness Tb III labels for in vitro and in vivo analysis of abnormal tissues 13,21,22 . Finally, Parker and coworkers have designed Eu III complexes staining the nucleoli of live cell lines such as NIH 3T3, HeLa, and HDF 23,24 .…”
Section: Introductionmentioning
confidence: 98%